STUDI KELAYAKAN PENDIRIAN PD. BPR BKK MANDIRAJA CABANG PAGEDONGAN DI BANJARNEGARA - Suliyanto, Suliyanto (Performance, 2010)
The purpose of this study is to analyze the feasibility of the establishment of PD. BPR BKK Mandiraja Pagedongan Branch in Banjarnegara. Some aspects are analyzed in this study are legal aspects, technical aspects, management aspects, market aspects and financial aspects. Legal aspects, technical aspects, management aspects, market aspects, analysed by descriptive-comparative analysis while financial aspect is analyzed by investment criterion analysis: Payback Period (PP), Net Present Value (NPV), Index Profitability (PI), and Internal Rate of Return (IRR). Based on the analyzis, it can be concluded that establishment of PD. BPR BKK Mandiraja Pagedongan Branch in Banjarnegara is feasible to be executed.